1992
DOI: 10.1182/blood.v80.9.2172.bloodjournal8092172
|View full text |Cite
|
Sign up to set email alerts
|

Breakpoints at 11q23 in infant leukemias with the t(11;19)(q23;p13) are clustered

Abstract: We have analyzed a series of nine infant leukemias that carry a t(11;19)(q23;p13). They had the morphologic features of acute lymphoblastic leukemia (ALL) and expressed markers typical of B-cell progenitor ALL or pre-B ALL; one coexpressed myeloid markers in addition to lymphoid markers (biphenotypic). Two probes (P/S4 and 98.40) subcloned from a yeast artificial chromosome (YAC) known to span the breakpoint in the t(4;11) were used to investigate DNA isolated from the leukemic cells of these patients. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The MLL gene is usually rearranged in these cases and the most common chromosomal partner site is 4q21, the site of the AF4/FEL gene (Gu et al , 1992; Kearney et al , 1992; Tkachuk et al , 1992) in the translocation t(4;11)(q21;q23). Southern analyses have demonstrated that breakpoints in different individuals and from different translocations cluster within a region <5.8 kb in length (Chen et al , 1991; Morgan et al , 1992). Molecular analysis of presentation material has demonstrated a higher incidence of rearrangement than detected by cytogenetic analysis.…”
Section: Rearrangements Involving Chromosome Band 11q23mentioning
confidence: 99%
“…The MLL gene is usually rearranged in these cases and the most common chromosomal partner site is 4q21, the site of the AF4/FEL gene (Gu et al , 1992; Kearney et al , 1992; Tkachuk et al , 1992) in the translocation t(4;11)(q21;q23). Southern analyses have demonstrated that breakpoints in different individuals and from different translocations cluster within a region <5.8 kb in length (Chen et al , 1991; Morgan et al , 1992). Molecular analysis of presentation material has demonstrated a higher incidence of rearrangement than detected by cytogenetic analysis.…”
Section: Rearrangements Involving Chromosome Band 11q23mentioning
confidence: 99%
“…Chromosome 11q23 is important as translocations occur here in both acute myeloid and lymphoblastic leukaemias (Rowley, 1993; Bernard and Berger, 1995; Rubnitz et al ., 1996; Look, 1997; Gilliland, 1998) as well as in therapy‐related leukaemias (DeVore et al ., 1989; Pui et al ., 1989; Cimino et al ., 1997; Nasr et al ., 1997; Rowley et al ., 1997; Sobulo et al ., 1997; Atlas et al ., 1998; Felix, 1998). Molecular cloning of various translocation breakpoints revealed a gene called MLL (also called ALL‐1 , HRX or HTRX ) in which the translocations occur (Ziemin‐van der Poel et al ., 1991; Djabali et al ., 1992; Gu et al ., 1992; Morgan et al ., 1992; Tkachuk et al ., 1992; Thirman et al ., 1993). The affected region of the MLL gene is fairly small, around exon 8, but the chromosomal translocations result in fusion with a range of genes from other chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of MLL breakpoints associated with clinical disease are found within an 8·3 kbp tract of MLL defined by BamH1 restriction sites that includes MLL exons 8–14 (Morgan et al , ; Thirman et al , ). Of note, those MLL fusions genes linked to both infant acute leukaemia (IAL) and therapy‐related acute myeloid leukamia (tAML) have their breakpoints primarily located in the 3′ region of the break cluster region (BCR) (Broeker et al , ; Cimino et al , ).…”
mentioning
confidence: 99%